Influence of the Filler’s Size on the Percolation Behavior in the Polyethylene Glycol/Carbon Nanotubes System - E.A. Lysenkov; V.V. Klepko; Yu.V. Yakovlev (Журнал нано- та електронної фізики)
The research of electric properties of the systems based on polyethylene glycol and carbon nanotubes (CNT) near-by the percolation threshold is done using the method of impedance spectroscopy. It is set that the percolation threshold for these systems substantially depends on the sizes of nanotubes. It is discovered that with the increase in the CNT diameter, the percolation threshold is increased. The dispersion parameters of nanotubes were calculated using theoretical model. The results of calculations and microphotographs testify to the high level of CNТ aggregates in the polymer nanocomposites based on polyethylene glycol.